2011
DOI: 10.1111/j.1399-5448.2011.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

The concerns of school staff in caring for children with diabetes in primary school

Abstract: Increased training for teachers having direct and current responsibility for children with diabetes was thought to lessen anxiety. Greater and more accessible knowledge about diabetes for all staff was requested. A range of practical management strategies were highlighted, including fostering good communication and teamwork between child, parent, school, and HCP. Professionals felt that support services would improve by using community-based dieticians and including psychological input into the diabetes team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 11 publications
(18 reference statements)
0
41
0
1
Order By: Relevance
“…Their daily presence at school or during insulin injections contributes to diabetes management . However, only 2 participants mentioned this support, showing that this is an issue in Brazilian schools and in other contexts . When the school nurse is present, an increase in insulin injections by the children is observed because they have the support and assistance from the nurse …”
Section: Discussionmentioning
confidence: 99%
“…Their daily presence at school or during insulin injections contributes to diabetes management . However, only 2 participants mentioned this support, showing that this is an issue in Brazilian schools and in other contexts . When the school nurse is present, an increase in insulin injections by the children is observed because they have the support and assistance from the nurse …”
Section: Discussionmentioning
confidence: 99%
“…Teachers and other school personnel may be hesitant to provide diabetes care due to feelings of inadequacy and lack of knowledge (Boden et al, 2012). Some concerns reported by teachers included the inability to identify the signs and symptoms of hypoglycemia and hyperglycemia as well as being able to properly treat either, if needed (Siminerio & Koerbel, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that teachers have concerns related to inexperience and lack of knowledge about long‐term illnesses . Earlier studies have also demonstrated that teachers are not adequately trained and prepared to manage emergencies dealing with long‐term illnesses . These facts seem to result in fear of litigation should something untoward occur …”
Section: Discussionmentioning
confidence: 99%
“…and prepared to manage emergencies dealing with longterm illnesses. [35][36][37][38] These facts seem to result in fear of litigation should something untoward occur. [35,39] These findings underscore the fact that teachers, despite being lay persons in relation to medicines, are having to deal with medication administration at school.…”
Section: Discussionmentioning
confidence: 99%